Seeddispersing vertebrates and the abiotic environment shape functional diversity of the pantropical Annonaceae - Cabral,A; Bender,IMA; Couvreur,TLP; Faurby,S; Hagen,O; Hensen,I; Kühn,I; RodriguesVaz,C; Sauquet,H; Tobias,JA; Onstein,RE (New Phytologist, 2025)
Mutualistic interactions between fruiting plants and frugivorous animals are shaped by interaction-relevant functional traits. However, it is unclear whether ‘trait matching’ underlies broad-scale relationships in plant and frugivore species and their functional diversity.We integrated novel trait data and global occurrences for c. 1900 species in a major tropical plant family (Annonaceae) with data for 7607 bird and mammal species, including 1418 frugivores, alongside data on the abiotic environment. We applied structural equation models to evaluate the direct and indirect drivers of global and continental variation in frugivory-related functional diversity in Annonaceae, and assessed frugivory-exclusive drivers through comparisons with non-frugivores.We show that global variation in Annonaceae frugivory-related functional diversity is influenced by species richness (SRic) and trait matching with co-occurring frugivorous mammals. Frugivorous birds and mammals indirectly influenced Annonaceae functional diversity at continental scales by affecting Annonaceae SRic. We found that climate, elevation, and seed dispersers jointly shaped Annonaceae diversity globally.Our results suggest that seed dispersal interactions with mammals are particularly important for shaping global variation in Annonaceae diversity, possibly through mutualistic co-evolutionary dynamics. However, distinct effects of frugivores on Annonaceae diversity across biogeographical realms suggest that biogeography modulates how mutualistic interactions promote diversity.